The Plaka petrified forest park in western Lesvos - Greece - Zouros, N.; Velitzelos, E.; Valiakos, I.; Labaki, O. (Bulletin of the Geological Society of Greece, 2007)
On the island of Lesvos, large accumulations of fossilised tree trunks comprise the Lesvos Petrified Forest a protected natural monument. Within the protected area of the Lesvos Petrified Forest Geopark, several fossil sites with impressive fossilized trees have been discovered along the coast. During the last few years, the Natural History Museum of the Lesvos Petrified Forest has conducted systematic scientific research on these sites. The coastal area ofPlaka was one of the main sites of research interest in order to explore the terrestrial and marine fossil sites. Several clusters of petrified trees have been found and identified in 45 different fossil sites. Some of them were standing while others were lying. The intact root systems of the standing trees provide proof that these trees were petrified in situ. Most of the trees are angiosperms and gymnosperms. The coastal landscape and its rich ecosystem, and the fossil sites, in combination with volcanic, tectonic and geomorphological structures, are basis of the rich geotouristic potential of the new Plaka Park, which has become an area for environmental education as well as a new geotouristic attraction.